2007
DOI: 10.1134/s1068162007060064
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequence-specific ligands: XIII. New dimeric Hoechst 33258 molecules, inhibitors of HIV-1 integrase in vitro

Abstract: Dimeric Hoechst 33258 molecules [dimeric bisbenzimidazoles (DBBIs)] that, upon binding, occupy one turn of the B form of DNA in the narrow groove were constructed by computer simulation. Three fluorescent DBBIs were synthesized; they consist of two bisbenzimidazole units tail-to-tail linked to phenolic hydroxy groups via penta- or heptamethylene or tri(ethylene glycol) spacers and have terminal positively charged N.N-dimethylaminopropyl carboxamide groups in the molecule. The absorption spectra of the DBBIs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…An alteration of absorption spectrum of ( Va ) in the presence of calf thymus DNA indicated the formation of their complex [31]. Chromosomes are identified in most of cytogenetic studies by the pattern of differential staining.…”
Section: Resultsmentioning
confidence: 99%
“…An alteration of absorption spectrum of ( Va ) in the presence of calf thymus DNA indicated the formation of their complex [31]. Chromosomes are identified in most of cytogenetic studies by the pattern of differential staining.…”
Section: Resultsmentioning
confidence: 99%
“…We determined the DB 3 P(n) localization in the DNA groove using the method of circular dichroism (CD) with DNA cholesteric liquid crystal dispersions (preparation of such dispersions was described in [15]) (Fig. 6).…”
Section: Physicochemical Studiesmentioning
confidence: 99%
“…Previously we described the design and synthesis of several sets of dimeric bisbenzimidazoles [12][13][14][15][16][17], analogues of the dimeric bisbenzimidazole motif of the uorescent AT-speci c Hoechst 33258 dye. These dimeric bisbenzimidazoles were synthesized with the goal of developing AT speci c ligands noncovalently binding to the dsDNA minor groove and occupying nearly one coil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this approach, a recent study reported the design of inhibitors that could potentially disrupt IN-DNA binding. 105,106 Fluorescent dye Hoechst 33258 is known to bind noncovalently and site-specifically to the minor groove of DNA, but derivatives are insoluble. Attempts at improving the solubility of these DNA binders led to the discovery of potent new IN inhibitors.…”
Section: Other Approaches To Inhibit Inmentioning
confidence: 99%